2020
DOI: 10.3136/fstr.26.527
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lipid Profile and Adipocyte Size in Rats Fed on High-fat Diet Using Camel Milk and Whey Protein Mixture

Abstract: The aim of this study was to examine the effect of oral administration of Camel milk (CM) and whey protein (WP) (1.5 % and 3.0 % in water) -either alone or in a mixture -on obesity parameters and lipid profile in rats fed on a high-fat diet. The results revealed that feeding rats on CM or WP significantly reduced body weight gain, adipocyte size and the weight of perirenal adipose tissue, especially when CM was mixed with 1.5 % WP. Feeding rats on CM, WP or a mixture of CM and WP led to a significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…The histopathological changes in treated groups with normal or low calorie formula of biscuits and crackers except for low calorie biscuit formula four as compared to that induced with high fat diet alone indicated marked protective effects of whey cheese and oat addition against weight gain. These results were previously supported by Althwab et al, (2020), who reported that whey supplementation efficacy in preventing overweight and obesity by lowering weight gain and serum levels of lipids.…”
Section: Lipid Profiles Of Different Groups: Regarding Serum Lipids R...supporting
confidence: 75%
“…The histopathological changes in treated groups with normal or low calorie formula of biscuits and crackers except for low calorie biscuit formula four as compared to that induced with high fat diet alone indicated marked protective effects of whey cheese and oat addition against weight gain. These results were previously supported by Althwab et al, (2020), who reported that whey supplementation efficacy in preventing overweight and obesity by lowering weight gain and serum levels of lipids.…”
Section: Lipid Profiles Of Different Groups: Regarding Serum Lipids R...supporting
confidence: 75%